Randai Training at Gandai Sindang Harapan Art Gallery, Rumah Gadang Mande Rubiah, South Pesisir Regency - Nursi Nursi; Solfema Solfema (Universitas Negeri Padang, 2020)
This research is motivated by the activity of randai participants in Kampung Sindang, who are mostly teenagers who are in Kampung Sindang, this may be because the implementation in Randai Training and the trainers use appropriate strategies, and there are also supporting and inhibiting factors in Randai training. In addition, there is also the uniqueness of randa training in Kampung Sindang, which is a divers randai movement and interesting kaba poetry so that enthusiastic participants in randai training, in participating in randai training, participants are required to wear scarves and skirts from long fabrics because that is the main requirement in randai training. This study aims to describe how the implementation of randai training, randai training strategies are userd, and the factors supporting and inhibiting randai training in Kampung Sindang, Nagari Sindang Lunang, Kabupaten Pesisir Selatan. The components of the implementation of randai training are the planning and companion stages and training strategies, namely the material used and taught, the methods used, the media used, and the evaluations used. This type of research uses a qualitative descriptive approach. Data collection techniques used, qualitative data reduction, data presentation, and drawing conclusions. The author’s findings, namely training material in the form of randai movenents in the form of “letok kuwau movements, somang bajapai, hari paneh, ratak kudo”, using pravtical methods and auditive media (reling on voice capabilities), and evaluations conducted by the by the trainer instructing participants to repeat randai movements after randai training done.Keywords: Implementation of Randai, Randai Strategies, Supporting and Inhibiting Factors